A comprehensive study on dynamic performance of ball bearing considering bearing deformations and ball-inner raceway separation. (15th February 2023) - Wang, Mingkai; Yan, Ke; Zhang, Xiaohong; Zhu, Yongsheng; Hong, Jun
Highlights: An improved dynamic model of ball bearing is proposed. This model considers bearing deformations and ball-inner raceway separation. A prediction method for the initial values is applied to solve dynamic model. The influence of deformations and ball-inner raceway separation is discussed. Abstract: In actual operation conditions, the bearing deformations caused by the change of assembly state play a major role in bearing dynamic performance, and the ball-inner raceway separation due to the insufficient preload or excessive external loads is also a key issue that limits the bearing service. In this paper, an improved nonlinear dynamic model of ball bearing considering bearing deformations and ball-inner raceway separation is proposed. Firstly, the relationships between the bearing deformations and bearing-shaft assembly state are directly derived according to the deformation compatibility condition, and the interaction and relative motions among various bearing components under the ball-inner raceway separation conditions are analyzed. Then a prediction method for the initial iterative values is used to calculate the dynamic model, and the calculation results are compared with the experimental data for verification. Finally, the variations of bearing deformations, contact properties, and cage skid under different factors are investigated. It is found that the bearing deformations affect the contact properties of ball-raceway, and the appropriate preload effectively improves the bearing service characteristics, especially under the ball-inner raceway separation conditions.